Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2217/fon-2021-0328
|View full text |Cite
|
Sign up to set email alerts
|

PD-(L)1 Inhibitors as Single-Agent or in Combination with Chemotherapy for Advanced, PD-L1-high Non-Small Cell Lung Cancer: A Meta-Analysis

Abstract: Introduction: The best treatment for advanced, PD-L1-high non-small-cell lung cancer remains a debated issue. Methods: A meta-analysis of randomized clinical trials (RCTs) was performed to compare the efficacy and safety of PD-(L)1 inhibitors alone or plus chemotherapy (CT) for advanced, PD-L1-high non-small-cell lung cancer. Results: 14 RCTs were included. The combination of a PD-(L)1 inhibitor with CT resulted in the improvement of progression-free survival (HR: 0.59; 95% CI: 0.43–0.79; p = 0.0005) and objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The addition of chemotherapy improved survival outcomes compared with standard chemotherapy, and to date, no head-to-head comparisons have been performed with ICI as single agents, which is of remarkable interest, especially for NSCLCs with high PD-L1 expression (≥50% tumor proportion score) [ 1 , 25 ]. In this setting, the combination strategy may prevent early progression and improve the response rate, and the decision may be driven by clinical conditions or high tumor burden [ 26 ]. It is unclear whether the PAPwCPS score may have a role in the decision-making process for therapy selection, but it should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of chemotherapy improved survival outcomes compared with standard chemotherapy, and to date, no head-to-head comparisons have been performed with ICI as single agents, which is of remarkable interest, especially for NSCLCs with high PD-L1 expression (≥50% tumor proportion score) [ 1 , 25 ]. In this setting, the combination strategy may prevent early progression and improve the response rate, and the decision may be driven by clinical conditions or high tumor burden [ 26 ]. It is unclear whether the PAPwCPS score may have a role in the decision-making process for therapy selection, but it should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an extended follow-up time more accurately reflects the true effects of both treatments. In a meta-analysis of PD-1/PD-L1 inhibitors as monotherapy or combined with chemotherapy in advanced non-small cell lung cancer (NSCLC), combinations of PD-1/PD-L1 inhibitors and chemotherapy improved PFS and ORR compared with monotherapy [ 40 ]. This inspired us to combine PD-1 inhibitors with traditional chemotherapy for the treatment of terminal or metastatic EC.…”
Section: Discussionmentioning
confidence: 99%
“…42 A recent meta-analysis of 14 randomized clinical trials evaluated the best treatment option for non-oncogeneaddicted advanced NSCLC with PD-L1 expression ≥50%. 43 The results evidenced that the addition of platinum-based CT to a PD-(L)1 inhibitor significantly improves both PFS ISSN: 1740-4398 REVIEW -How to manage non-oncogene-addicted NSCLC drugsincontext.com (HR 0.59, 95% CI 0.43-0.79; p=0.0005) and ORR (RR 1.66, 95% CI 1.14-2.42; p=0.008) compared to PD-(L)1 inhibitors as single agents, though it has no statistically significant impact on OS (HR 0.99, 95% CI 0.77-1.27; p=0.95). On the other hand, expectedly, the addition of CT determined a higher risk of grade ≥3 treatment-related adverse events.…”
Section: Biomarker For Treatment Selectionmentioning
confidence: 99%
“…On the other hand, expectedly, the addition of CT determined a higher risk of grade ≥3 treatment-related adverse events. 43 These studies indicate that selecting patients who should be treated with ICIs alone or combined with CT remains challenging and needs a thorough evaluation. Higher PD-L1 expression cut-offs may offer more reliability, as demonstrated by the improved outcomes obtained in patients with NSCLC with PD-L1 expression ≥90% reported in the retrospective analysis by Aguilar et al 44 and by the analysis of the EMPOWER-Lung 1, which showed increasing ORR, PFS and OS according to higher PD-L1 levels.…”
Section: Biomarker For Treatment Selectionmentioning
confidence: 99%